Diagnostic clinical application of two-color fluorescence in situ hybridization that detects chromosome 1 and 17 alterations to direct touch smear and liquid-based thin-layer cytologic preparations of endometrial cancers. Issue 1 (1st January 2005) - Susumu, N.; Aoki, D.; Noda, T.; Nagashima, Y.; Hirao, T.; Tamada, Y.; Banno, K.; Suzuki, A.; Suzuki, N.; Tsuda, H.; Inazawa, J.; Nozawa, S.
Abstract : We performed two-color fluorescence in situ hybridization (FISH) on direct touch smears and liquid-based thin-layer (ThinPrep) cytological preparations of endometrial tumors to detect alterations of chromosome 1 and 17 that present with high incidence in endometrial cancers. The DNA probes used for two-color FISH analysis were a combination of the probes designed for 17cen (cCI 17-321) and 17p13.3 ( D17S34 ), and a combination of the probes designed for 1q12 ( D1Z1 ) and 1p36 (cCI1-5335). Numerical or structural alterations of chromosome 1 and/or 17 were detected in 95% (19 of 20 cases) of the direct touch smears obtained from endometrial cancer, while these alterations were also detected in 93% (12 of 13 cases) of samples obtained from grade 1 endometrioid adenocarcinoma cases, including three cases that could not be diagnosed as positive by conventional Papanicolaou cytopathologic staining. Using ThinPrep cytopathologic preparations, numerical or structural abnormalities were found in 26 (90%) and five (100%) cases, respectively, of samples obtained transcervically from 29 endometrial cancer and five atypical endometrial hyperplasia cases. Therefore, two-color FISH may be a useful diagnostic method for endometrial adenocarcinoma and premalignant lesions that demonstrate only slight cellular atypia in conventional cytopathologic preparations.